Advanced engine technology - Heisler, Heinz (SAE International, Elsevier, 1995)
Valves and camshafts - Camshaft chain belt and gear train drives - Engine balance and vibration - Combustion chamber design and engine performance - Induction and exhaust systems - Supercharging systems - Carburetted fuel systems - Petrol injection systems - Ignition systems - Engine testing equipment - Diesel in-line fuel injection pump systems - Diesel rotary and unit injector fuel imjection pump systems - Emission control - Cooling and lubrication systems - Alternative power sources.